Long-term prognosis and cost-effectiveness of left ventricular assist device as bridge to transplantation: A systematic review. (15th May 2017) - Seco, Michael; Zhao, Dong Fang; Byrom, Michael J.; Wilson, Michael K.; Vallely, Michael P.; Fraser, John F.; Bannon, Paul G.
Abstract: Background: This systematic review aimed to evaluate the clinical outcomes and cost-effectiveness of left ventricular assist devices (LVADs) used as bridge to transplantation (BTT), compared to orthotopic heart transplantation (OHT) without a bridge. Method: Systematic searches were performed in electronic databases with available data extracted from text and digitized figures. Meta-analysis of short and long-term term post-transplantation outcomes was performed with summation of cost-effectiveness analyses. Results: Twenty studies reported clinical outcomes of 4575 patients (1083 LVAD BTT and 3492 OHT). Five studies reported cost-effectiveness data on 837 patients (339 VAD BTT and 498 OHT). There was no difference in long-term post-transplantation survival (HR 1.24, 95% CI 1.00–1.54), acute rejection (HR 1.10, 95% CI 0.93–1.30), or chronic rejection and cardiac allograft vasculopathy (HR 0.99, 95% CI 0.73–1.36). No differences were found in 30-day post-operative mortality (OR 0.91, 95% CI 0.42–2.00), stroke (OR 1.64, 95% CI 0.43–6.27), renal failure (OR 1.43, 95% CI 0.58–3.54), bleeding (OR 1.56, 95% CI 0.78–3.13), or infection (OR 2.44, 95% CI 0.81–7.38). Three of the five studies demonstrated incremental cost-effectiveness ratios below the acceptable maximum threshold. The total cost of VAD BTT ranged from $316, 078 to $1, 025, 500, and OHT ranged from $179, 051 to $802, 200. Conclusion: LVADs used as BTT did not significantly alter post-transplantation long-term survival, rejection, and post-operative morbidity. LVAD BTT may be cost-effective, particularly in medium and high-risk patients with expected prolonged waiting times, renal dysfunction, and young patients.